2005
DOI: 10.4269/ajtmh.2005.73.16
|View full text |Cite
|
Sign up to set email alerts
|

Antigenicity, Immunogenicity, and Protective Efficacy of Plasmodium Vivax Msp1 Pv200l: A Potential Malaria Vaccine Subunit

Abstract: Abstract. The merozoite surface protein 1 (MSP-1) is expressed in all Plasmodium species and is considered a major malaria vaccine candidate. We found that MSP-1 from Plasmodium vivax (PvMSP-1) contains a region of significant sequence homology with the 190L subunit vaccine derived from the P. falciparum MSP-1. The fragment, termed Pv200L, was expressed as a recombinant protein in Escherichia coli (rPv200L) and used to asses its immunologic relevance as a vaccine target. A cross-sectional, seroepidemiologic st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
117
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(121 citation statements)
references
References 33 publications
2
117
0
2
Order By: Relevance
“…26 It was further shown that that T cell response and antibodies against MSP1 were induced in human clinical trials by using P. falciparum MSP-1, in which epitopes responsible for cytokine production and memory response development were localized to the 33-kDa region of MSP-1 42 . 27,28 Hitherto, most of the studies on MSP-1 33 have focused on P. falciparum, P. vivax, or P. yoelii, but few on P. knowlesi. A large amount of P. knowlesi MSP-1 33 is required for its biochemical, structural, and immunologic studies.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…26 It was further shown that that T cell response and antibodies against MSP1 were induced in human clinical trials by using P. falciparum MSP-1, in which epitopes responsible for cytokine production and memory response development were localized to the 33-kDa region of MSP-1 42 . 27,28 Hitherto, most of the studies on MSP-1 33 have focused on P. falciparum, P. vivax, or P. yoelii, but few on P. knowlesi. A large amount of P. knowlesi MSP-1 33 is required for its biochemical, structural, and immunologic studies.…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Hitherto, most of the studies on MSP-1 33 have focused on P. falciparum, P. vivax, or P. yoelii, but few on P. knowlesi. A large amount of P. knowlesi MSP-1 33 is required for its biochemical, structural, and immunologic studies. In this study, recombinant MSP-1 33 of P. knowlesi was expressed and purified by using an Escherichia coli system.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations